Evaluation of MSME Financial Performance Based on ASIARA Daily Revenue Data - Zahra Salsa Bella (Journal Tourism Nomic, 2026)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in encouraging economic growth and creating jobs, especially in the culinary sector which has relatively stable market demand. This study aims to evaluate the financial performance of ASIARA MSMEs based on the analysis of daily income data. The research uses a quantitative approach with a descriptive method. The data used is secondary data in the form of daily sales recapitulation obtained through observation and documentation techniques. Data analysis was carried out using descriptive statistics to determine total income, average income, and income fluctuation patterns during the study period. The results showed that the income of ASIARA MSMEs fluctuated during the observation period, but in general it was still at a relatively stable level. The total income during the 18 days of observation reached IDR 3,430,000 with an average daily income of IDR 190,555. The highest income was recorded at IDR 300,000, while the lowest income was IDR 80,000. The variation in income was influenced by changes in the number of customers and market conditions on a given day. The results of the study also show that systematic recording and recapitulation of sales can help business actors in monitoring revenue developments and evaluating business financial performance. Therefore, daily sales data analysis can be one of the simple but effective approaches in improving financial management and business decision-making in MSMEs.